Pediatric cough as a symptom: Tips for management - Bavdekar, Sandeep B; Vora, Agam; Karekar, Sonali (Indian Journal of Child Health, 2022)
Cough in children and adults is a commonly witnessed symptom that can be related to a serious underlying disease. It is a reflex phenomenon that protects the airways and lungs by eliminating mucus, inhaled irritants, pathogens, and particulates and further helps in clearing out the air spaces of accumulated secretions. However, cough in children and adults has some notable differences based on various parameters, including duration, symptoms witnessed, duration, and etiology. Therefore, the tools and processes commonly employed for evaluating cough in adults may not apply to pediatric patients. Furthermore, the management of cough, in general, should be based on the etiology instead of the underlying disease condition. There is a relative paucity of data related to pediatric cough in comparison to adult cough, making the management of cough challenging. This article provides a comprehensive review of cough management in children in Indian scenarios.